Parotid Lipoma: Case Report - Maryam Maghbol; Mohammad Javad ashraf; Negar Azarpira (Fasa University of Medical Sciences, 2014)
Background & Objective: Lipoma (a benign tumor composed of adipose tissue) is the most common benign mesenchymal tumors in soft tissue but it is very rare in the parotid gland. Case: We reported a 54 years old man with parotid gland lipoma. Parotid gland lipoma usually originates from the superficial lobe. Superficial parotidectomy has been considered as the choice method of the treatment. Result: lipoma, as a prevalent tumor of the soft tissue, is rarely seen in salivary glands.